2009
DOI: 10.1152/ajpgi.90553.2008
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus casei strain Shirota prevents indomethacin-induced small intestinal injury: involvement of lactic acid

Abstract: Inflammatory responses triggered by activation of the lipopolysaccharide (LPS)/Toll-like receptor (TLR) 4 signaling pathway are a key mechanism in nonsteroidal anti-inflammatory drug-induced enteropathy. The aim of this study was to investigate the probiotic effect of Lactobacillus casei strain Shirota (LcS) on indomethacin-induced small intestinal injury. Rats pretreated with viable LcS or heat-killed LcS once or once daily for a week were administered indomethacin by gavage to induce injury. Anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 35 publications
4
109
0
6
Order By: Relevance
“…Escherichia coli Nissle 1917 (EcN) SN stimulated the secretion of the anti-inflammatory cytokines interleukin (IL)-10 and IL-6, 20 in peritoneal cells of rats, while factors released by Lactobacillus casei Shirota inhibited indomethacin-induced nuclear factor kappa B (NFκB) activation and increases in tumor necrosis factor (TNF)-α mRNA expression. 21 The anti-inflammatory properties were attributed to the bacteria-derived lipopolysaccharide and lactic acid production for EcN SN and L. casei Shirota, respectively. 20,21 Similar to EcN SN, Bacillus coagulans secreted factors have been reported to promote IL-10 expression, and inhibit oxidative stress-induced formation of reactive oxygen species (ROS).…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli Nissle 1917 (EcN) SN stimulated the secretion of the anti-inflammatory cytokines interleukin (IL)-10 and IL-6, 20 in peritoneal cells of rats, while factors released by Lactobacillus casei Shirota inhibited indomethacin-induced nuclear factor kappa B (NFκB) activation and increases in tumor necrosis factor (TNF)-α mRNA expression. 21 The anti-inflammatory properties were attributed to the bacteria-derived lipopolysaccharide and lactic acid production for EcN SN and L. casei Shirota, respectively. 20,21 Similar to EcN SN, Bacillus coagulans secreted factors have been reported to promote IL-10 expression, and inhibit oxidative stress-induced formation of reactive oxygen species (ROS).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations into the beneficial effects of probiotics and mechanisms of probiosis have demonstrated that several probiotic species produce metabolites that modulate the host's mucosal immune system. For example, L-lactic acid production by Lactobacillus casei strain Shirota may work via Toll-like receptor 4 (TLR4) signaling to suppress indomethacin-induced myeloperoxidase activity and tumor necrosis factor (TNF) production by human myeloid (THP-1) cells in a rat model of small intestine injury (4). Bifidobacterium breve strain BbC50 and Streptococcus thermophilus strain St065 also secrete small, digestive-enzyme-resistant metabolites that were found to be able to inhibit TNF production from lipopolysaccharide (LPS)-activated THP-1 cells (5).…”
mentioning
confidence: 99%
“…Several studies have demonstrated beneficial effects of probiotics, including Lactobacillus acidophilus and Lactobacillus casei, in experimental models of NSAID enteropathy [30,35]. There have also been human studies demonstrating preventative effects of a single probiotic (L. casei) [36] or of a cocktail of probiotics [37] against NSAID-induced small intestinal injury.…”
Section: Can Probiotics Protect Against Nsaid Enteropathy?mentioning
confidence: 99%
“…It is also possible that metabolites from bacteria can influence these processes. For example, Watanabe et al [35] highlighted the possibility that lactic acid released by L. casei strain Shirota might contribute to the ability of that probiotic to reduce the severity of indomethacin-induced intestinal damage in rats. Kinouchi et al [30] demonstrated that supernatants from cultures of L. acidophilus or B. adolescentis, but not the bacteria themselves, could significantly reduce NSAID-induced intestinal damage.…”
Section: Do Substances Released From Probiotics Account For Their Benmentioning
confidence: 99%